Sharia Financial Literacy As a Moderating Variable of The Influence of Sharia Financial Management on Investment Interest in The Sharia Capital Market : Penelitian - Dwi Rohmawati Khasanah; Hamdiah; Afrizal; Wiljan Atfentia Kotngoran; Lisye Magdalena Liur (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research is quantitative with an explanatory approach (Mardiana 2016). The data used in this study are primary data obtained from BFI Syariah managers throughout Indonesia through online questionnaires (Jonathan Sarwono 2016). The data obtained was analyzed using the Smart PLS 4.0 analysis tool. The result in this article show